Impact of Agricultural Land Loss on Rural Livelihoods in Peri-Urban Areas: Empirical Evidence from Sebougou, Mali - Brahima Coulibaly; Shixiang Li (Land, 2020)
This study was part of a larger analysis of the framework of sustainable rural livelihoods in the face of urban sprawl in peri-urban rural areas of Mali. Contrary to the existing literature, which has mostly focused on issues of land rights in Mali due to the fact of urbanization, this study analyzed the consequences of urbanization in the city of Ségou on the major sources of livelihoods for residents in the neighboring rural municipality of Sebougou. Three villages in the municipality of Sebougou were selected due to the fact of their proximity to the city of Ségou. We interviewed 120 randomly sampled family heads using a structured questionnaire. The respondents were owners of farmlands or people who had lost their land as a result of urbanization. We analyzed the data using multi-linear and logistic regression models. The results showed that age, occupation, land size, and level of education had significant positive impacts on the farmers’ annual family income, while family size and gender exerted negative effects. Low-yield lands and youth emigration increased the likelihood of farmers losing their lands to urbanization. Conversely, land size, yearly income, and age had negative predictive effects on agrarian land loss. The results highlight the need for land management authorities to implement policies to protect agricultural land.